Pronomina Penunjuk dalam Bahasa Minangkabau - Iman Laili (Fakultas Bahasa dan Seni UNP, 2012)
Demonstrative pronouns in Minangkabau language consist of demonstrative pronouns and adverbs of place. Demonstrative pronouns consist of demonstrative pronoun that refers to reference that is near to the speaker or writer and demonstrative pronoun that refers to a reference that is far from the speaker. Adverbs of place also consist of adverbs of place indicating the place close to the speaker and adverbs of place indicating the place far from the speaker. Key words: demonstrative pronoun, general demonstrative pronoun, demonstrative pronoun indicating places